Analysis on Individual Characteristics Impact towards Employee Career Development at UIN Kiai Haji Achmad Siddiq Jember - Abdul Rahim (The Faculty of Education and Teaching Training, 2023)
Abstract The rapid flow of information and development of technology and science have brought changes to individual life patterns. In order to maintain self-existence, every individual desires career improvemnet as it affects their income. Career development and utilization of human resources are organizational needs. This study uses a quantitative approach. The research population includes all employees having civil servant status within State Islamic University of Kiai Haji Achmad Siddiq Jember. The data collection methods used were questionnaires, interviews and documentaries. The data was analayzed through descriptive analysis and Multiple Linier Regression Analysis which aims to look for relationship patterns that can be described mathematically between one dependent variable (Y) and several independent variables (X). Based on the results of analysis and hypothesis testing, it shows that the independent variable consists of expertise (X1), level of education (X2) and work experience (X3) influence simultaneously towards career. The degree of the contribution or influence of the independent variable is . 64.8% while the remaining 35.2%. influenced by other factors outside the model. P value for the skill variable (X1) = 0.903 so it is not significant at ? = 0.05, which means that the skill variable (X1) does not have a significant individual effect on the career development of employees at Kiai Haji Achmad Siddiq Jember State Islamic University. Likewise, P value for the education variable (X2) = 0.001 so it is significant at ? = 0.05 which means that the education variable (X2) has a significant individual influence on employee career development. Meanwhile, the P value for the work experience variable (X3) = 0.023 so it is significant at ? = 0.05 which means that the work experience variable (X3) has a significant individual influence on the career development of UIN Kiai Haji Achmad Siddiq Jember employees. Derasnya arus informasi dan pesatnya perkembangan teknologi dan ilmu pengetahuan membawa perubahan bagi pola kehidupan individu. Agar eksistensi diri tetap terjaga, maka setiap individu menginginkan karirnya meningkat karena karir seseorang juga mempengaruhi penghasilan. Pengembangan karir dan pemanfaatan sumber daya manusia merupakan kebutuhan organisasi. Penelitian ini menggunakan pendekatan kuantitatif. Populasi penelitian mencakup seluruh karyawan yang berstatus PNS dalam lingkup Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember. Metode pengumpulan data yang digunakan adalah angket, interview dan dokumenter. Teknik analisa datanya menggunakan analisis deskriptif dan analisis Multiple Linier Regression Analysis yang bertujuan untuk mencari pola hubungan yang dapat digambarkan secara matematis antara satu variable tak bebas (Y) dengan beberapa variabel bebas (X). Berdasarkan hasil analisa dan pengujian menunjukkan variabel bebas yang terdiri dari keahlian (X1), tingkat pendidikan (X2) dan pengalaman kerja (X3) berpengaruh secara bersama-sama (simultan) Besarnya kontribusi atau pengaruh variabel bebas sebesar. 64,8 % sedangkan sisanya sebesar 35,2 %. dipengaruhi oleh faktor-faktor lain diluar model. Nilai Pvalue untuk variabel keahlian (X1) = 0.903 sehingga tidak signifikan pada ? = 0,05 yang berarti bahwa variabel keahlian (X1) tidak berpengaruh signifikan secara individu terhadap pengembangan karier karyawan. Nilai Pvalue untuk variabel pendidikan (X2) = 0.001 sehingga signifikan pada ? = 0,05 yang berarti bahwa variabel pendidikan (X2) berpengaruh signifikan secara individu terhadap pengembangan karier karyawan. Sedangkan Nilai Pvalue untuk variabel pengalaman kerja (X3) = 0.023 sehingga signifikan pada ? = 0,05 yang berarti bahwa variabel pengalaman kerja (X3) berpengaruh signifikan secara individu terhadap pengembangan karier karyawan UIN Kiai Haji Achmad Siddiq Jember.